(untitled) (UKH Journal of Social Sciences, 2021)
The present study aims at investigating the use of prosodic features by Kurdish EFL undergraduates in their face-to-face interactions inside/outside the classroom from the university instructors’ perspectives. The study hypothesizes that the majority of Kurdish EFL undergraduates are not fully aware of the fact that any misuse of prosodic features would probably affect the emotions, feelings, and attitudes that the face-to-face interaction is intended to convey. Building on an analysis of a questionnaire given to 54 university instructors at 10 Iraqi Kurdistan Region different universities, the study concludes that the majority of problems the students face can be related to the misuse of stress, intonation, and other prosodic features. Therefore, EFL instructors should pay more attention to make students learn how to use prosodic features and enable them to send messages adequately while engaging in face-to-face interactions. This would require special classes about prosodic features so that EFL students can overcome the misuse they have in face-to-face communication. This is inevitable because accuracy and fluency in communication require EFL students to master both features: segmental and suprasegmental. The reason behind this necessity could be attributed to the fact that broken and/or incorrect pronunciation can be considered as one of the most prominent factors behind misunderstandings in communication.